Upregulation of CB2 receptors in reactive astrocytes in canine degenerative myelopathy, a disease model of amyotrophic lateral sclerosis - María Fernández-Trapero; Francisco Espejo-Porras; Carmen Rodríguez-Cueto; Joan R. Coates; Carmen Pérez-Díaz; Eva de Lago; Javier Fernández-Ruiz (The Company of Biologists, 2017)
Targeting of the CB2 receptor results in neuroprotection in the SOD1G93A mutant mouse model of amyotrophic lateral sclerosis (ALS). The neuroprotective effects of CB2 receptors are facilitated by their upregulation in the spinal cord of the mutant mice. Here, we investigated whether similar CB2 receptor upregulation, as well as parallel changes in other endocannabinoid elements, is evident in the spinal cord of dogs with degenerative myelopathy (DM), caused by mutations in the superoxide dismutase 1 gene (SOD1). We used well-characterized post-mortem spinal cords from unaffected and DM-affected dogs. Tissues were used first to confirm the loss of motor neurons using Nissl staining, which was accompanied by glial reactivity (elevated GFAP and Iba-1 immunoreactivity). Next, we investigated possible differences in the expression of endocannabinoid genes measured by qPCR between DM-affected and control dogs. We found no changes in expression of the CB1 receptor (confirmed with CB1 receptor immunostaining) or NAPE-PLD, DAGL, FAAH and MAGL enzymes. In contrast, CB2 receptor levels were significantly elevated in DM-affected dogs determined by qPCR and western blotting, which was confirmed in the grey matter using CB2 receptor immunostaining. Using double-labelling immunofluorescence, CB2 receptor immunolabelling colocalized with GFAP but not Iba-1, indicating upregulation of CB2 receptors on astrocytes in DM-affected dogs. Our results demonstrate a marked upregulation of CB2 receptors in the spinal cord in canine DM, which is concentrated in activated astrocytes. Such receptors could be used as a potential target to enhance the neuroprotective effects exerted by these glial cells.